Manufacturing Consent, Legitimizing Power: The Dialectic of Media Discourse in Narrating Sheikh Hasina’s Fall - Shaikh, Hasan (International Journal of Media and Communication Research, 2026)
Power is rarely taken in silence but is legitimated in words. In the contemporary power conflicts, Sheikh Hasina’s fall appears not only as a political event but also as a well-narrated spectacle, constructed, distorted, and legitimated through the architecture of media discourse. Drawing on the Propaganda Model, this analysis examines how The Daily Star, Bangladesh’s most prominent English-language newspaper, crafts a regime change narrative through carefully designed rhetorical strategies that mask elite and transnational power interests while shaping public consent. Using the tools of language, it paints regime change not as a messy, bitter rupture, but as a natural and necessary correction. To do this, it systematically mutes the voice of Hasina, while amplifying foreign voices, military figures, and the opposition. This is not an oversight; it is a deliberate choice. The media turns military leaders into democratic heroes and protests into powerful myths, all to make this specific version of events feel inevitable and right. Editorial “flak” emerges not as explicit censorship but as tonal calibration and deliberate sourcing choices, effectively shielding dominant actors from critique. In the end, the study shows a media that has traded its watchdog role for that of a master storyteller, building public consent for a narrative that serves elite interests.